Comparison of perception of stress and consumption of anxiolytics in hospital and out-hospital conditions: a cross-sectional study - Jovanović, Željko; Pešut, Sara; Miletić, Bojan (Frontiers in Public Health, 2024)
BACKGROUND: The workplace is a place where medical workers are exposed to extreme stress, particularly during medical emergencies or events of epidemic or pandemic proportions. Anxiolytic therapy is often used to overcome professional challenges. Deepening knowledge about the prevalence of the use of anxiolytics and the perception of stress among medical workers enables the timely recognition of problems and the preparation of measures to improve the working conditions and quality of life of medical workers. The study's primary objectives are to compare stress factors in the workplace in hospital and outpatient conditions and investigate whether there were differences in the usage of anxiolytics among healthcare professionals in and out of the hospital. STUDY DESIGN: Cross-sectional research. MATERIALS AND METHODS: The research involved 159 healthcare professionals in Slavonski Brod: 96 employees of the General Hospital "Dr. Josip Benčević" and 63 employees of the Health Center and the Institute for Emergency Medicine of Brodsko-Posavina County. Respondents were able to participate in the study by filling out questionnaires online. The questionnaire was designed to be voluntary and anonymous and contained 53 questions. RESULTS: Statistically significant differences were shown in the perception of stress, which is greater in hospital staff, than in the difference between stressors in the workplace, where hospital staff showed higher values in all categories, but three factors are more significant differences: "Organization of the workplace and financial issues", "Conflicts and communication at work" and „Professional and intellectual requirements". There are significant differences in the frequency of using anxiolytics with the assistance of a psychiatrist. Working conditions have a much greater impact on the perception of stress and life satisfaction in hospital staff, while in hospital staff only a weak link between the perception of stress and life satisfaction is expressed. Anxiolytics are consumed by 27.10% of hospital workers and 23.80% of outside-the-hospital workers. CONCLUSION: The consumption of anxiolytic drugs by healthcare professionals in hospital and outpatient conditions does not make a significant difference, but they do have statistically significant differences in their perception of stress.